“A STUDY ON EFFECTIVE TRAINING AND DEVELOPMENT IN INSURANCE AGENCIES AT CHENNAI” - Elantheraiyan, Dr.P.; Thandayuthapani, Dr. S. (The journal of contemporary issues in business and government, 2022)
The research article titled, “A Study On Effective Training And Development In Insurance Agencies At Chennai” aims at analyzing the training and development methods which is giving by insurance agencies at Chennai. The research study will helpful to find the the employees and agents satisfaction level of existing training methodologies practiced in the insurance agencies. The research study is based on the primary data collected through questionnaire method. The questionnaire consists of well-structured open-ended, closed- ended, dichotomous, and multiple choice questions. The sample size is 120 to be considered. Convenient random sampling technique is applied for selecting sample size of the respondent.